2015
DOI: 10.1016/j.ijmachtools.2015.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of material deformation mechanism in double side incremental sheet forming

Abstract: This is a repository copy of Investigation of material deformation mechanism in double side incremental sheet forming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 29 publications
2
60
0
Order By: Relevance
“…The deformation mechanism and fracture behaviour of double point incremental forming has been investigated based on the membrane analysis and experimental work. It was found that by using different supporting force and tool shift the FLCF can be increased as compared with SPIF [11]. An analytical model was developed with the consideration of bending effect and strain hardening to describe the localised deformation in ISF.…”
Section: Introductionmentioning
confidence: 99%
“…The deformation mechanism and fracture behaviour of double point incremental forming has been investigated based on the membrane analysis and experimental work. It was found that by using different supporting force and tool shift the FLCF can be increased as compared with SPIF [11]. An analytical model was developed with the consideration of bending effect and strain hardening to describe the localised deformation in ISF.…”
Section: Introductionmentioning
confidence: 99%
“…In recent development, a number of variations of the ISF processes were proposed, such as the conventional singlepoint incremental forming (SPIF) [4], the two-point incremental forming (TPIF) [5], the hybrid incremental forming [6], and the double-side incremental forming (DSIF) [7]. In all these processes, a rigid tool has to be employed to deform the sheet blank.…”
Section: Introductionmentioning
confidence: 99%
“…Bagudanch et al (2014) concluded that the Marlow and the rule of mixture material models could be used to describe viscoelastic and softening and permanent set effects, respectively, to predict the behavior of a part formed by ISF. Lu et al (2015) investigated that by employing two forming tools on each side of the sheet, DSIF process can provide additional process flexibility, compared to the conventional single point incremental forming (SPIF) process, therefore to produce complex geometries without the need of using a backing plate or supporting die. Shrivastava and Tandon (2015) performed experiments on samples heat treated at different temperatures and hence, different grains to evaluate the effect of forming forces.…”
mentioning
confidence: 99%